Closing words in the Holy Quran Semantic study (Journal of the College of Basic Education, 2022)
The closing words are a general designation for the words included in this closing; Since I find that printThe seal, according to linguists and commentators, has almost the same meaning, which is to cover the thing and authenticate itthat nothing enters it; However, stamping is more general than stamping 0, and rin is easier than stampingand seal; Because it is the sin that distorts the heart and with its abundance prevails in the heart, so faith does not enter it; which is rustlocated on the heart; As for the closure, it is more severe, while the closure is the most powerful and impactfulAnd I find that among these words there are those who came in different forms, and they are the words (printed and sealed) and eachA formula of signification different from the other as required by the denominator.